Exercise in African American and White Colorectal Cancer Survivors: A Mixed-Methods Approach. Issue 4 (October 2018) - Ray, Andrew D.; Masucci Twarozek, Annamaria; Williams, Brian T.; Erwin, Deborah O.; Underwood, Willie; Mahoney, Martin C.
Abstract : Background: African American (AA) colorectal cancer (CRC) survivors tend to be more obese and less physically active than white survivors. Purpose/Objective: To test the feasibility of an aerobic exercise program as well as explore perceptions about supervised exercise among AA CRC survivors. Methods: A prospective supervised exercise intervention performed on a cycle ergometer 2 d/wk for 12 weeks. Peak ( O2peak ) and submaximal exercise (Six-Minute Walk Test [6MWT]) along with questionnaires (36-Item Short Form Health Survey [SF-36], Memorial Sloan Kettering Cancer Center Bowel Function Instrument [BFI], Functional Assessment of Cancer Therapy–Colorectal (FACT-C) and Fatigue (FACIT-F), and Brief Symptom Inventory [BSI]). A second group of survivors participated in an interview evaluating perceptions regarding exercise. Design: Prospective case series and qualitative interview. Setting: Research university and academic medical center. Patients: AA and white CRC survivors. Results: Quantitative: A total of 237 letters were mailed to CRC survivors (112 whites, 126 AAs). From the letters, 25 whites and 15 AAs expressed interest; only 5 whites (4.5%) and 4 AAs (3.2%) enrolled. Two AA and 5 white survivors (7/9) finished the program. There was an improvement in peak exercise ( P = .011) and quality of life (QOL) (SF-36 total, P = .035) posttraining. Qualitative: 30 CRC survivors (12 AAs and 18 whites) participated in qualitative interviews and selected comorbidity, motivation, and location as primary barriers to exercise. Limitations: Small sample size. Conclusions: Recruiting CRC survivors (regardless of race) into an exercise program is challenging; however, there are exercise and QOL benefits associated with participation. Barriers to exercise are similar between AA and white CRC survivors.